2000
DOI: 10.1111/0021-8294.00017
|View full text |Cite
|
Sign up to set email alerts
|

Religious Consolation Among Men and Women: Do HealthProblems Spur Seeking?

Abstract: While most religions provide a meaning system that helps people cope with personal problems, there has been relatively little research on how and why men and women seek religious consolation and comfort. Data from a national longitudinal survey, Americans' Changing Lives, Waves I and II, were used to examine whether physical and mental health problems precipitate seeking religious consolation. The findings indicate that seeking religious consolation is most likely among those who identify with and practice a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(87 citation statements)
references
References 50 publications
4
80
1
2
Order By: Relevance
“…Finally, although it has been found that women are more likely than men to seek comfort through religion (Ferraro and Kelley-Moore 2000), and thus, may be expected to emotionally profit from an extrinsic religious orientation, which orients individuals to seek the benefits of religious engagement, the present study did not find a significant interaction among sex, depressive symptoms, and religious orientation. While the lack of significance may be due to power issues, it also is possible that religiosity is so deeply ingrained in the lives of Southeastern Americans (Pew Research Center 2015) that all individuals in this area of the country will derive benefits from their religious faith, irrespective of gender.…”
Section: Discussioncontrasting
confidence: 94%
“…Finally, although it has been found that women are more likely than men to seek comfort through religion (Ferraro and Kelley-Moore 2000), and thus, may be expected to emotionally profit from an extrinsic religious orientation, which orients individuals to seek the benefits of religious engagement, the present study did not find a significant interaction among sex, depressive symptoms, and religious orientation. While the lack of significance may be due to power issues, it also is possible that religiosity is so deeply ingrained in the lives of Southeastern Americans (Pew Research Center 2015) that all individuals in this area of the country will derive benefits from their religious faith, irrespective of gender.…”
Section: Discussioncontrasting
confidence: 94%
“…Women, furthermore, are more likely to seek consolation through religion (Ferraro and Kelley-Moore 2000), suggesting that the use of positive religious coping may serve as a buffer against substance use for females, though not for males.…”
Section: Religious Coping and Substance Usementioning
confidence: 99%
“…In this review, religiousness was considered a protective factor against suicide, drug abuse and alcohol, delinquent behavior, marital satisfaction, psychological suffering and psychoses 1 . Some researchers have observed increased religiousness during negative life events, which include falling ill [1][2][3][4] . On the other hand, the connection with religion may be both a source of relief and discomfort depending on how the person relates to it 3,5 .…”
Section: Introductionmentioning
confidence: 99%